Assessment of Aesthetic Results of 100 Patients Who Underwent Rhinoplasty—Rhinoplasty Outcome Evaluation. Issue 9 (September 2017) - Kotzampasakis, Dimitrios; Mantalos, Panagiotis; Kotzampasakis, Stylianos; Danias, Nikolaos; Nikolopoulos, Thomas
Abstract : Background: To assess the long-term aesthetic results of rhinoplasty and predict the final outcome. Methods: The sample was composed of 100 patients (34 men and 66 women) between 23 and 57 years old (mean, 34.8) operated on exclusively for aesthetic reasons. The time elapsed from the operation ranged from 3 to 13 years with a mean of 6.8 years. The study used Rhinoplasty Outcome Evaluation questionnaire, a simple, reliable, validated, and widely used inventory. Results: The vast majority of patients (93%) were satisfied postoperatively with scores > 50% (67 patients had scores > 80%). Only 7 patients had scores less than 50%. The mean score was 82.4 ± 1.7% with a median of 87%. In addition, it seems that the results of the operation remain high through time with a small decline along age groups and years elapsed. Women were found more satisfied than men ( P = 0.03). Conclusions: The study concludes that the results of aesthetic rhinoplasty, if performed by skilled and experienced surgeons, are very satisfying and stable throughout time.